Basic Life Support Education to Increase the Knowledge, Attitudes and Skills of Members Marine and Air Police Directorate - Hartati, Ratih; Natalia, Siska; Suangga, Fitriani (Sarana Ilmu Indonesia (salnesia), 2024)
Abstract Drowning is one the most common accident in Riau Island. Drowning can cause hypoxia, acidosis lactate and hypothermia, this can result in cardiovascular dysfunction, ie heart rhythm disorders to cardiac arrest. Basic life support is needed to restore breathing and circulation fungction of a person. Marine and Air Police Directorate Riau Islands is the front line of providing assistance and rescue at sea and waters. Previously there was no proper BLS training, therefore the training is needed to prepare first responders. This study aimed to determine of Basic Life Support education to increase on knowledge, attitudes and skills member of Marine and Air Police Directorate Riau Islands. This research used a quantitative method with a research design with pre experimental design research design used with one group pre-post design without control. The total number of samples taken with purposive randomsampling of Subditpatroliairud Members and Police Boat members with 50 subjects and data analysis using Paired T-Test. Theaverage before and after education BLS were 58,13-83,33 for knowledge, 78,77-83,33 on attitude, 29,84-79,23 on skill. Paired T-Test on knowledge, attitudes and skills with a p-value of 0,000 (p-value<0,05) therefore Ha is accepted. Therefore, there is an effecton BLS training on improving knowledge, attitudes and skills member of Marine and Air Police Directorate.